Low weight baby´s feeding cultural practices and family´ s contribution for the nursing care in the domiciliary space: preview note - Sandra Teixeira de Araújo Pacheco; Ivone Evangelista Cabral (Universidade Federal Fluminense, Escola de Enfermagem Aurora de Afonso Costa, 2008)
In the infantile population group, the baby that was born of low weight presents peculiarities and own nutritional demands to promote the well - being and growth and healthy development. In that way, they need restricted monitoring of health, for having larger possibility to present metabolic disturbances, difficulties to control his/her temperature and to feed, facts those that expose them to larger falling sick ill risk. The study objectives are: to reveal the familiar group´ s care practices of the low weight baby in the feeding management, to analyze the articulations manners of those practices with the relatives' decision in these babies' feeding and to interpret those practices and those manners of articulations in the light of the family knowledge. The chosen method for the development of this study will be the Creative Sensitive. The collection of data will be realized in the child's house near to his/her responsible and family. For the results analysis we will make a data mapping obtained in the field works, (tapes transcription, re - reading of the material, reports and data organization of the participant observations) characterizing like this the stage of the data ordination. Afterwards the pre-analysis of the data obtained in the groups to verify which the empiric material that was produced. This pre-analysis will orientate the researcher in the choice of the analytical method in the field of the discourse analysis. The results will be interpreted by the light of the theoretical reference of Vygostsky, Geertz and of the concept of Health Promotion.